PROBLEMATIKA GURU PENDIDIKAN AGAMA HINDU SELAMA MENGIKUTI PROGRAM PENDIDIKAN PROFESI GURU DALAM JABATAN (PPG DALJAB) SECARA DARING - Ni Nyoman Mariani (Guna Widya: Jurnal Pendidikan Hindu, 2024)
The aim of this research is to find out the problems of Hindu Religious Education teachers while taking PPG Daljab online. This type of research is descriptive research with a qualitative approach. The informants in this research were Hindu Religious Education teachers throughout the Republic of Indonesia who took online Professional Teacher Education (PPG Daljab). The technique for determining informants is purposive sampling. Data collection techniques using questionnaires, and qualitative data analysis techniques with stages; data collection, data reduction, data presentation, and drawing conclusions The results of the research show that the problems experienced by Hindu Religious Education teachers while taking part in PPG Daljab online include: problems originating from the students themselves, problems related to the curriculum, problems with advice and infrastructure, problems related to management in the implementation of PPG Daljab , as well as problems related to the environment